Effectiveness of Virtual Reality and Interactive Simulators on Dental Education Outcomes: Systematic Review - Moussa, Rania; Alghazaly, Amira; Althagafi, Nebras; Eshky, Rawah; Borzangy, Sary (European Journal of Dentistry, 2021)
In recent years, virtual reality and interactive digital simulations have been used in dental education to train dental students before interacting with real patients. Scientific evidence presented the application of virtual technology in dental education and some recent publications suggested that virtual and haptic technologies may have positive effects on dental education outcomes. The aim of this systematic review was to determine whether virtual technologies have positive effects on dental education outcomes and to explore the attitudes of dental students and educators toward these technologies. A thorough search was conducted in PubMed, Scopus, MEDLINE (via EBSCO), The Cochrane Library (via Wiley), Web of Science Core Collection (via Thomson Reuters), and Dentistry and Oral Science source (via EBSCO) using the keywords (student, dental) AND (education, dental) AND (virtual reality) OR (augmented reality) OR (haptics) OR (simulation) AND (dentistry) OR (dental medicine). The quality of the reported information was assessed following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) statement for systematic reviews. A total of 73 publications were considered for this review. Fifty-two of the selected studies showed significant improvement in educational outcomes and virtual technologies were positively perceived by all the participants. Within the limitations of this review, virtual technology appears to improve education outcomes in dental students. Further studies with larger samples and longer term clinical trials are needed to substantiate this potential positive impact of various virtual technologies on dental education outcomes.
Keywords: augmented reality; simulation; dental education; haptics; students; dental; virtual reality; education